Analisis Pengaruh Perceived Usefulness, Perceived Ease Of Use, Behavioral Intention To Use, Terhadap Actual System Use Dalam Menggunakan Sistem Esensus Pada AJB Bumiputera 1912 Kantor Cabang Wlingi - Evita Liana Sukma; Aditya Rachmadi; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Esensus is a mobile-based information system applied to the AJB Bumiputera 1912 Wlingi Branch office to help agents report the latest data that is still active. In its implementation, Esensus, AJB Bumiputera 1912 Wlingi Branch Office, started in February 2019 and there are still complaints from agents as users. Evaluation needs to be done so get a recommendation for improvements to improve of Esensus acceptance. This research uses modified Technology Acceptance Model (TAM) using four variables: Perceived Usefulness, Perceived Ease Of Use, Behavioral Intention To Use and Actual System Use. These variables were examined to describe user's acceptance of Esensus using descriptive statistical analysis. Data retrieval is done using offline questionnaires and interviews. The population used in this research are all agents of AJB Bumiputera 1912 Wlingi Branch office which once used Esensus with a sample of 36. The results of this research showed that variables Perceived Usefulness (76,70%), Perceived Ease Of Use (78,07%), Behavioral Intention To Use (80,80%) and Actual System Use (78,80%) belongs to the high category. From the results of the research, the recommendations were compiled to improve the acceptance of Esensus.